2000
DOI: 10.3109/10428190009060322
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Trial of Multiple Dose131Iodine-MAb LL2 (CD22) in Patients with Recurrent Non-Hodgkin's Lymphoma

Abstract: The purpose of this to evaluate in a phase I/II study the efficacy and toxicity of a multi-dose administration of 131I labeled CD22 monoclonal antibody (131I-MAb-LL2) in escalating dose cohorts administered to relapsed non-Hodgkin's lymphoma (NHL) patients. Twenty-one patients with relapsed NHL received one of four dose levels of 131-MAb-LL2 administered in a twice weekly pattern. Starting with dose level 2, the patients also received 20 mg of unlabeled LL2 prior to each radiolabeled dose administered. Previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Previous studies have evaluated murine and humanized forms of an anti-CD22 antibody both preclinically and clinically, as a carrier of radionuclides for NHL imaging and therapy (42)(43)(44), as well as a conjugate with toxins [ricin (45)(46)(47), pseudomonas exotoxin (48), or RNase (49)] for therapy. Results of these trials with one radioimmunoconjugate form of the antibody (42,43) suggested that the unlabeled Fig. 2 OR rates by dose for evaluable patients with DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated murine and humanized forms of an anti-CD22 antibody both preclinically and clinically, as a carrier of radionuclides for NHL imaging and therapy (42)(43)(44), as well as a conjugate with toxins [ricin (45)(46)(47), pseudomonas exotoxin (48), or RNase (49)] for therapy. Results of these trials with one radioimmunoconjugate form of the antibody (42,43) suggested that the unlabeled Fig. 2 OR rates by dose for evaluable patients with DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…The first clinical studies of the LL2 construct were trials evaluating the murine version as a radioimmunoconjugate for tumor imaging (Juweid et al, 1995(Juweid et al, , 1999Behr et al, 2002) or as radioimmunotherapy (Siegel et al, 1991;Kreitman et al, 1993;Behr et al, 1999Behr et al, , 2002Juweid et al, 1999;Linden et al, 1999Linden et al, , 2002Linden et al, , 2005Vose et al, 2000;Goldenberg, 2001Goldenberg, , 2003Postema et al, 2003;Sharkey et al, 2003Chatal et al, 2005;. Other toxin-conjugate forms have been developed and tested only pre-clinically to date, such as those that include Pseudomonas exotoxin (Newton et al, 2001a, b) and amphibian RNase (Leonard et al, 2005a, b;Newton et al, 2001a, b).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Therapy was well tolerated, with doselimiting toxicity being myelosuppression. Subsequently, the use of 131 I-murine LL2 IgG in a multiple-dosing scheme was reported by Vose et al (2000), and objective responses were noted in 7/21 patients. Humanization of the antibody (into epratuzumab) was then performed to minimize immunogenicity and to optimize its pharmacokinetics, safety and efficacy (Leonard et al, 2003).…”
Section: Anti Cd22 Radioimmunotherapy In Nhlmentioning
confidence: 99%
“…This therapy targets the CD20 antigen present on most B-cell lymphomas and has been shown to be effective against low-grade and transformed low-grade NHL in both nonmyeloablative 3 and myeloablative (followed by autologous stem cell transplant) 4 protocols. Other RITs in development include another anti-CD20 MAb Y2B8 radiolabeled with yttrium-90, 5 Lym-1 (which targets the HLA-DR10 antigen on the surface of malignant B-lymphocytes) radiolabeled with iodine-131, 6 or copper-67 7 and LL2 (which targets the CD22 antigen on B-cell lymphomas) radiolabeled with iodine-131 8 or yttrium-90. 9 Initial RIT treatments were performed on an inpatient basis.…”
mentioning
confidence: 99%